2014
DOI: 10.5539/ijef.v6n10p76
|View full text |Cite
|
Sign up to set email alerts
|

How Do Auditors Increase Substantially Firm Value?

Abstract: This study used Tobin's Q to examine the relationship between various types of auditors (e.g., industry expert, supply chain auditor) and market participants in order to determine the effects on firm value. Our results indicate that market participants highly value Big 4 supply chain auditors with industry experience and that these impressions are extended to their evaluation of their clients. We also found that only in the subsample of long-term auditor-client relationships were Big 4 supply chain auditor wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 22 publications
5
22
1
Order By: Relevance
“…Audit quality was also found to have no effect on the value of the firm. This finding is different from Afza and Nazir (2013), Wang and Huang, (2014), and Ugwunta et al, (2018) who find audit quality can have a positive impact on firm value. There are still many cases that ensnare the independent auditor causing the market to assume that the independent auditor cannot be used as a signal.…”
Section: Regression Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Audit quality was also found to have no effect on the value of the firm. This finding is different from Afza and Nazir (2013), Wang and Huang, (2014), and Ugwunta et al, (2018) who find audit quality can have a positive impact on firm value. There are still many cases that ensnare the independent auditor causing the market to assume that the independent auditor cannot be used as a signal.…”
Section: Regression Resultscontrasting
confidence: 87%
“…Finally, audit quality is an independent party that can be a control mechanism and reduce agency conflicts that occur between firms and stakeholders outside the firm. Many studies have shown the influence of audit quality on firm value (Afza and Nazir, 2013;Wang and Huang, 2014;and Ugwunta et al, 2018). High quality audits increase market confidence in the credibility of financial statements presented by the firm.…”
Section: Measurementmentioning
confidence: 99%
“…Previous research has conducted many studies on audit quality, such as Gaynor et al (2016) which examines the relationship with the quality of financial statements, earnings quality (Reyad, 2013), corporate performance (Elewa and El-Hadad., 2019), auditor reputation (Skinner and Srinivasan, 2012), and earnings management (Inaam et al, (2012), Chi et al, (2011)). Wang and Huang (2014) explain that audit quality has an important impact on firm value. However, there are only few studies that conduct a comprehensive analysis of audit quality and firm value.…”
Section: Introductionmentioning
confidence: 99%
“…Most research discusses the relationship between audit quality and financial report quality, but there is a few research that focuses on audit quality and firm value (Wang and Huang, 2014). Hamdan et al (2012) explain that the increasing accounting scandal in the capital market increases awareness of the importance of audit quality.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the earnings and book value of equity, which are audited by BIG4 auditors, could explain more variations in the stock return of companies than non-BIG4 auditors do. Reference [22] also reveals that market participants highly value BIG4 auditors with industrial experience. BIG4 auditors are, therefore, associated with higher companies' value.…”
Section: Introductionmentioning
confidence: 99%